The Differences Between Hand and Hand Plus Vibration Forming on Mechanical Properties of Oil Palm Empty Fruit Bunch Fibreboards - Zakaria, Sarah Yasmien; Hasniza Abu Bakar, (Recent Trends in Civil Engineering and Built Environment, 2022)
The growth in the production of used palm oil has caused the environmental problem and promotes abundance of oil palm empty fruit bunch (OPEFB) fibre. OPEFB fibre is one of the lignocellulosic materials that could replace other natural cement fibreboard products. The objectives of this research were to analyse the differences of hand and hand plus vibration forming for mechanical properties of empty fruit bunch cement board (EFBCB) and to propose the most suitable forming method in the fabrication process of EFBCB that contributes to optimum mechanical properties of the samples. The study used Ordinary Portland Cement, EFB fibre, water and NaOH in the fabrication of the EFBCB which involved two different methods which were hand forming and hand plus vibration forming method. A total of 12 sample boards with 350mm x 350mm x 12mm size were used with a constant density of 1300 kg/m3. The ratio used for cement and EFB fibre was 3:1 respectively. Testing of Modulus of Rupture (MOR), Modulus of Elasticity (MOE) and Internal Bonding (IB) were conducted in the study. All measurements were carried out according to the BS EN 310:1993 and BS EN 319:1993. Results showed that the mean values when using hand plus two minutes time of vibration were the highest for MOE, MOR and IB which were 4915.67 N/mm2, 13.08 N/mm2, and 0.44 N/mm2 respectively. This showed that the MOE and MOR have complied to the BS EN 310:1993 while IB did not comply to the BS EN 319:1993. This may highly due to the proportion of the cement component. As the proportion of cement component is higher, the void space decreases. Although IB did not comply to the standard used, it was still accepted due to the nearest value of 0.5N/mm2 which was the minimum requirement in the standard. Therefore, the second minute of hand forming plus vibration method is being proposed in the fabrication process of EFBCB that contributed to optimum mechanical properties in terms of MOE and MOR of the sample.The growth in the production of used palm oil has caused the environmental problem and promotes abundance of oil palm empty fruit bunch (OPEFB) fibre. OPEFB fibre is one of the lignocellulosic materials that could replace other natural cement fibreboard products. The objectives of this research were to analyse the differences of hand and hand plus vibration forming for mechanical properties of empty fruit bunch cement board (EFBCB) and to propose the most suitable forming method in the fabrication process of EFBCB that contributes to optimum mechanical properties of the samples. The study used Ordinary Portland Cement, EFB fibre, water and NaOH in the fabrication of the EFBCB which involved two different methods which were hand forming and hand plus vibration forming method. A total of 12 sample boards with 350mm x 350mm x 12mm size were used with a constant density of 1300 kg/m3. The ratio used for cement and EFB fibre was 3:1 respectively. Testing of Modulus of Rupture (MOR), Modulus of Elasticity (MOE) and Internal Bonding (IB) were conducted in the study. All measurements were carried out according to the BS EN 310:1993 and BS EN 319:1993. Results showed that the mean values when using hand plus two minutes time of vibration were the highest for MOE, MOR and IB which were 4915.67 N/mm2, 13.08 N/mm2, and 0.44 N/mm2 respectively. This showed that the MOE and MOR have complied to the BS EN 310:1993 while IB did not comply to the BS EN 319:1993. This may highly due to the proportion of the cement component. As the proportion of cement component is higher, the void space decreases. Although IB did not comply to the standard used, it was still accepted due to the nearest value of 0.5N/mm2 which was the minimum requirement in the standard. Therefore, the second minute of hand forming plus vibration method is being proposed in the fabrication process of EFBCB that contributed to optimum mechanical properties in terms of MOE and MOR of the sample.